PENGARUH REPUTASI UNDERWRITER DAN AUDITOR, FINANCIAL LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP UNDERPRICING - Rita Mulyani (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
These days, capital fulfilment is one of the main important part to develop business, and lot of ways being used to achieve it. One of the example is stocks public offering through stock exchange, or by other name a company is go public. When a company decided to go public, the first process is IPO (Initial Public Offering) which means their shares are being offered to public through prime market, it was then continued being trade in stock exchange (secondary market). If stock price during the IPO is lower than the stock price on the first day in secondary market for the same stock, then an underpricing phenomenon is happening. Underpricing is an IPO phenomenon in the capital markets and have been proven by researchers in many countries. The purpose of this research to determine the effect of underwriter reputation, auditor reputation, financial leverage and size of the company towards underpricing. The population of this research is all companies that perform IPO at Indonesia Stock Exchange during 2010-2015 period, and sample is collected by using purposive sampling, resulting in 84 companies as sample. In this research used quantitative methods with the technique of multiple linear regression that is Ordinary Least Square (OLS) analysis with the help of Eviews 8 analysis tools. The research results shows that the variables auditor reputation, financial leverage and size of the company have significant influence partially towards underpricing, while underwriter reputation haven’t influence towards underpricing. The next results shows that the variables underwriter reputation, auditor reputation, financial leverage and size of the company have significant influence simultaneously towards underpricing. Keywords : Underpricing, Underwriter Reputation, Auditor Reputation, Financial, Leverage, Size Company